Repetition Without Repetition: Challenges in Understanding Behavioral Flexibility in Motor Skill - Ranganathan, Rajiv; Lee, Mei-Hua; Newell, Karl M. (Frontiers in Psychology, 2020)
A hallmark of skilled motor performance is behavioral flexibility – i.e., experts can not only produce a movement pattern to reliably achieve a given task goal, but also possess the ability to change that movement pattern to fit a new context. In this perspective article, we briefly highlight the factors that are critical to understanding behavioral flexibility, and its connection to movement variability, stability, and learning. We then address how practice strategies should be developed from a motor learning standpoint to enhance behavioral flexibility. Finally, we highlight some important future avenues of work that are needed to advance our understanding of behavioral flexibility. We use examples from sport as a context to highlight these issues, especially in regard to elite performance and development.